KONTRIBUSI PAJAK DAERAH DAN RETRIBUSI DAERAH TERHADAP PENDAPATAN ASLI DAERAH (PAD) KABUPATEN SIDOARJO - SHELLA YONANDA P A (Jurnal Pendidikan Ekonomi (JUPE), 2013)
Regional autonomy is an instrument to achieve development which aims to increase the community's economy. The success of local governments to regulate and manage the region can be seen from the dependence of local governments to the central government that can be marked on the amount of regional incomes, regional taxes and retributions which are the backbone of the regional revenue sources that should be increased every year. This study evaluated the contribution of Local Taxes and Retributions Revenue towards Sidoarjo Regional which aims to find out 1) General overview of tax revenues and retributions in Sidoarjo Region from 2008 to 2012, 2) Management procedures, taxes and retributions on the Department of Revenue, Finance and Asset Management Sidoarjo Region, 3) The contribution of taxes and retributions in Sidoarjo Region and 4) the contribution of each sector to the taxes and retributions. This type of research is combined with Sequantial explanatory models. The data used in this research are time series, which are the data taxes, retributions and Sidoarjo Regional Income from 2008 to 2012. This study uses the analysis of Share Growth for quantitive method and triangulation method for qualitative analysis and combinations. The results of quantitative analysis showed that local tax revenue from the year 2008 to 2012, every year has increased and local taxes may provide a contribution of 48,94 percent in each year, while the revenue from retribution income fluctuate, due to changes in the Act that requires the reduction of types of retribution, there by reducing the amount of revenue in 2009, the average contribution generated by 19,4 percent of the total revenue in Sidoarjo Region. The results of qualitative analysis showed that the management of local taxes and levies in DPPKA Sidoarjo covers collection, payment and supervision. Tax payment mechanisms designed to facilitate tax payers to pay liabilities not matched by public awareness the importance of paying taxes. Keywords: Local Taxes, Local Retributions and Regional Income